Strategi pengembangan budidaya perikanan air tawar di Kecamatan Dimembe Kabupaten Minahasa Utara Provinsi Sulawesi Utara - Worang, Bacthiyar C.G.S.; Sinjal, Hengky J.; Monijung, Revol D. (e-Journal BUDIDAYA PERAIRAN, 2018)
The objectives of this research were to study the profile of freshwater fish culture in Dimembe District, Analyse the prospects for the development of aquaculture in Dimembe District,Â  determine cultivation development strategy that is suitable with the condition and potential of Dimembe District. The method used in this research was descriptive using data in the last 5 years. Data were analysed using quantitative and qualitative descriptive analysis and SWOT analysis. Fish farmers in Dimembe District amounted to 226 people and the location of water quality supports the business of freshwater fish cultivation of indigo and carp in Dimembe District. Internal factors included business location, water quality, local government support, existance of BPBAT. Factors weaknesses were availability of less deed, and lack of human resources. External factors affecting the development of fish farming in Dimembe District consist of opportunity factor that were high fish selling value, high market share, big business opportunity, government policy. Treat factors: theft and security. Strategy steps for developing fish farming business in Dimembe District could be conducted by increasing the production of tilapia fish and goldfish, providing training on freshwater fishery cultivation and maintainng the quality of fish farming products, making agreement among farmers in maintaining the security of pond cultivation.Â Keywords: Dimembe District, freshwater cultivation, fish farmers, SWOT analysis